Language switching as a strategy of communication in modern-day interactions - Megawati, Soekarno; Ting, Su Hie (2013)
The study examined the communication strategies used by healthcare trainees in oral presentations. The specific objectives of the study were to: (1) determine the frequency in which various communication strategies were used; and (2) compare communication strategies used by the healthcare trainees in monologues and dialogues during the oral presentations. The trainees were final year diploma students in healthcare. Their project Presentation and the Question-and-Answer session of 11healthcare trainees were recorded and transcribed for analysis. The results showed that language switching is the main communication strategy relied upon to clarify jargon, clarify issues and emphasise key points during the oral presentation. The monologue has a higher frequency of language switching but the chunks of switching are smaller, as compared to the dialogues which have fewer instances of language switching because the chunks are larger. The findings indicate that when language proficiency is limited, language switching may compensate for linguistic inadequacies and enhance negotiation of meaning.